Effect of Cistanche deserticola on Rumen Microbiota and Rumen Function in Grazing Sheep - Zhang, Xiaoyun; Liu, Xulei; Chang, Shenghua; Zhang, Cheng; Du, Wuchen; Hou, Fujiang (Frontiers in Microbiology, 2022)
For a long time, veterinary drugs and chemical additives have been widely used in livestock and poultry breeding to improve production performance. However, problems such as drug residues in food are causing serious concerns. The use of functional plants and their extracts to improve production performance is becoming increasingly popular. This study aimed to evaluate the effect of Cistanche deserticola in sheep feed on rumen flora and to analyze the causes to provide a theoretical basis for the future use of Cistanche deserticola as a functional substance to improve sheep production performance. A completely randomized experimental design was adopted using 24 six-month-old sheep males divided into four groups (six animals in each group) which were fed a basic diet composed of alfalfa and tall fescue grass. The C. deserticola feed was provided to sheep at different levels (0, 2, 4, and 6%) as experimental treatments. On the last day (Day 75), ruminal fluid was collected through a rumen tube for evaluating changes in rumen flora. The test results showed that Prevotella_1, Lactobacillus, and Rikenellaceae_RC9_gut_group were the dominant species at the genus level in all samples. Lactobacillus, Rikenellaceae_RC9_gut_group, Ruminococcaceae_NK4A214_group, Butyrivibrio_2, and Christensenellaceae_R-7_group differed significantly in relative abundance among the treatment groups. The polysaccharides in C. deserticola was the major factor influencing the alteration in rumen flora abundance, and had the functions of improving rumen fermentation environment and regulating rumen flora structure, etc. Hence, C. deserticola can be used to regulate rumen fermentation in grazing sheep to improve production efficiency.